Study of Cytotoxic Effects of Benzonitrile Pesticides. (3rd August 2015) - Lovecka, Petra; Thimova, Marketa; Grznarova, Petra; Lipov, Jan; Knejzlik, Zdenek; Stiborova, Hana; Nindhia, Tjokorda Gde Tirta; Demnerova, Katerina; Ruml, Tomas
Abstract : The benzonitrile herbicides bromoxynil, chloroxynil, dichlobenil, and ioxynil have been used actively worldwide to control weeds in agriculture since 1970s. Even though dichlobenil is prohibited in EU since 2008, studies addressing the fate of benzonitrile herbicides in the environment show that some metabolites of these herbicides are very persistent. We tested the cytotoxic effects of benzonitrile herbicides and their microbial metabolites using two human cell lines, Hep G2 and HEK293T, representing liver and kidneys as potential target organs in humans. The cell viability and proliferation were determined by MTT test and RTCA DP Analyzer system, respectively. The latter allows real-time monitoring of the effect of added substances. As the cytotoxic compounds could compromise cell membrane integrity, the lactate dehydrogenase test was performed as well. We observed high toxic effects of bromoxynil, chloroxynil, and ioxynil on both tested cell lines. In contrast, we determined only low inhibition of cell growth in presence of dichlobenil and microbial metabolites originating from the tested herbicides.